Silicon in Agriculture 2015
DOI: 10.1007/978-94-017-9978-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Mediated Tolerance to Salt Stress

Abstract: Silicon (Si) has widely been reported to increase plant tolerance and/or resistance to salt (salinity) stress, but the underlying mechanisms remain poorly understood. This chapter reviews the updated knowledge concerning Si and salt (salinity) interactions in higher plants. Based on the current literature, it seems that (1) silica deposited in the apoplast as SiO 2 opal or phytolith can enhance water retention by inhibiting transpirational water loss, thus reducing salt-induced osmotic stress, and (2) soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 76 publications
(177 reference statements)
2
18
0
2
Order By: Relevance
“…It was observed that the yield reduction was associated with the reduction of the number, size, and weight of tuber per plant [99]. trials showed that the addition of K2O3Si increased the potato yield by 12.3% [102]. In the case of zinc, application of 1500 ppm of nano-ZnO on corn plants enhanced the yield by 42% as compared to control plants [103].…”
Section: Impacts Of Soil Salinity On Number and Yield Of Potato Tubersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the yield reduction was associated with the reduction of the number, size, and weight of tuber per plant [99]. trials showed that the addition of K2O3Si increased the potato yield by 12.3% [102]. In the case of zinc, application of 1500 ppm of nano-ZnO on corn plants enhanced the yield by 42% as compared to control plants [103].…”
Section: Impacts Of Soil Salinity On Number and Yield Of Potato Tubersmentioning
confidence: 99%
“…On the contrary, supplementary application of Zn, Si, B, and zeolite nanoparticles apparently improve the morphological and physiological attributes and alleviate salt stress [67,101]. In potato, long-term field trials showed that the addition of K 2 O 3 Si increased the potato yield by 12.3% [102]. In the case of zinc, application of 1500 ppm of nano-ZnO on corn plants enhanced the yield by 42% as compared to control plants [103].…”
Section: Impacts Of Soil Salinity On Chemical Compositions Of Potato mentioning
confidence: 99%
“…71,74,75 In addition, Si nanoparticles reduce sodium uptake and translocation while increasing potassium uptake and translocation under salt stress. 76,77 Salinity and drought are major challenges in agriculture that limit crop production. Therefore, the beneficial impacts of silica and silicon nanoparticles on plant growth and development can potentially address adverse effects of climate changes, such as uneven rainfall and rising temperatures, that lead to enhanced evaporation of water from the soil surface.…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…Notably, silica NPs also stimulate antioxidant enzymes to support improved seedling growth and tolerance under biotic and abiotic stresses [ 12 , 13 , 78 , 178 , 228 ]. They also inhibit Na uptake and its distribution while enhancing K uptake and accumulation [ 229 , 230 ]. As a result, the favorable effects of Si and Si NPs on plant growth and development may confer an ability to mitigate adverse impacts of climate change in years to come, for example, inconsistent rainfall, elevated or cold temperatures, and excess evaporation from the soil surface [ 78 ].…”
Section: Long-term Application Of Nano-fertilizers and Its Responses In Agriculturementioning
confidence: 99%